2016
DOI: 10.1002/yea.3149
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of heterologous α‐amylase production in two expression platforms dedicated for Yarrowia lipolytica: commercial Po1g–pYLSC (php4d) and custom‐made A18–pYLTEF (pTEF)

Abstract: In view of the constantly increasing demand for cost-effective, low-energy and environmentally friendly industrial processes and household care products, enzyme production occupies an essential place in the field of biotechnology. Along with increasing demand for industrial and household care enzymes, the demand for heterologous expression platforms has also increased. Apart from the conventional hosts, e.g. Escherichia coli, Saccharomyces cerevisiae and Pichia pastoris, routinely used in heterologous protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 65 publications
1
22
0
Order By: Relevance
“…Consistently, our previous studies have shown that such a mode of cultivation had beneficial effect on the production of heterologous alpha‐amylase by Y . lipolytica , as the titer of the extracellular protein was increased by 160 fold (max activity 22,979.2 AU L −1 AUl −1 h −1 AUl −1 h −1 ; Celińska, Borkowska, & Białas, ), when compared with previously obtained result in batch cultivation (142.84 AU L −1 AUl −1 h −1 AUl −1 h −1 ; Celińska, Borkowska, & Białas, ). Another interesting example of fed‐batch cultures optimization was presented in a series of papers by (Chang, Ryu, Park, & Kim, ; Chang, Ryu, Park, Kim, & Ogrydziak, ; Kim et al, ), which concerned production of rice alpha‐amylase in recombinant Y .…”
Section: Resultsmentioning
confidence: 45%
“…Consistently, our previous studies have shown that such a mode of cultivation had beneficial effect on the production of heterologous alpha‐amylase by Y . lipolytica , as the titer of the extracellular protein was increased by 160 fold (max activity 22,979.2 AU L −1 AUl −1 h −1 AUl −1 h −1 ; Celińska, Borkowska, & Białas, ), when compared with previously obtained result in batch cultivation (142.84 AU L −1 AUl −1 h −1 AUl −1 h −1 ; Celińska, Borkowska, & Białas, ). Another interesting example of fed‐batch cultures optimization was presented in a series of papers by (Chang, Ryu, Park, & Kim, ; Chang, Ryu, Park, Kim, & Ogrydziak, ; Kim et al, ), which concerned production of rice alpha‐amylase in recombinant Y .…”
Section: Resultsmentioning
confidence: 45%
“…Surprisingly, micro-/macro-SIT assays were in this case more sensitive to glucoamylase activity which, taken together with the results presented in (Fig. 4b), clearly show that constituents of the crude culture media disallow accurate assessment of TlGAMY activity. This in turn, also explains poor performance of macro-/micro-SNT assays shown in (Fig.…”
Section: Resultssupporting
confidence: 52%
“…One of the factors contributing to such an outcome could be formation of the insoluble precipitate encountered in the reactions with the crude culture media supernatants. In the macro-scale, the precipitate could be removed by simple centrifugation of the processed samples, as we did previously (Celińska et al 2015, 2016a, b, 2017). Nevertheless, additional step obviously disrupts rapid character of the methods, and thus disqualifies it from high-throughput screening of crude culture media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strains subjected to this analysis were confirmed to bear an estimated single copy of the heterologous expression cassette, using RTqPCR on genomic DNA (Additional File_3), as described previously [42]. Gene expression analysis was conducted in growth phase-synchronized cultures to minimize variability of the analysis [43].…”
Section: Expression Level Of Heterologous Genes Located In Tu1 and Tu2mentioning
confidence: 99%